Effect of integrated nutrient management on nutrient uptake and economics of fertilizer use in rice cv. NERICA 10 (Journal of the Bangladesh Agricultural University, 2016)
The integrated use of chemical and organic fertilizers can help in sustainable and environmentally sound nutrient management of soils. A study was conducted in the farmers field of Godaghari, Rajshahi from February to May 2012 to investigate the effect of integrated nutrient management on nutrient uptake by rice cv. NERICA 10 and economization of inputs. Six treatments viz. T1 = Control, T2 = RFD for MYG + cowdung @ 5 t ha-1, T3 = RFD for HYG, T4 = RFD for HYG + cowdung @ 5 t ha-1, T5 = RFD for HYG + cowdung @ 5 t ha-1 based on IPNS, and T6 = RFD for HYG + 10% excess fertilizer of HYG were used. The experiment was laid out in a randomized complete block design with three replications. Results showed that the uptake of N, P, K, S, Ca and Mg by both grain and straw of rice were statistically significant due to use of integrated nutrient management. The highest nutrient uptake was recorded from the treatment T5 and the lowest value was obtained from control. Combined application of cowdung @ 5 t ha-1 along with recommended chemical fertilizers based on IPNS was more economic compared to other treatments because maximum benefit cost ratio was calculated from this treatment. The overall results suggest that integrated nutrient management can be used as an alternate option of chemical fertilization to achieve maximum yield, nutrient uptake and cost of return for rice cv. NERICA 10 cultivation.J. Bangladesh Agril. Univ. 12(2): 273-277, December 2014